Modernisation through Railways: Economic and Social Change in the Ottoman Empire in the Nineteenth Century - Demirci, Sevtap; Cosar, Nevin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
In the nineteenth century, significant developments in transport and transport infrastructure technologies led to drastic changes not only in countries' economies but also in their societies. The European world economy absorbed the Ottoman Empire into its ambit and railway construction initiated by Europeans also shaped the nature and direction of social and economic changes in the vast territory that the Empire had controlled. The purpose of this paper is to analyse the impact of railways on Ottoman society modernization. The paper investigates how economic and social changes took place in traditional life in the empire and how and to what extent the lives and consumption patterns of Anatolian people were changed by the construction of railways.
Keywords: Area Studies